Analisis Perlindungan Hukum terhadap Keselamatan dan Kesehatan Kerja di PT Geo Dipa Energi Dieng - Idellia, Almira Salma; Nugroho, Asianto; Hermawan, Sapto (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Occupational Safety and Health (OSH) is a crucial aspect of the geothermal energy industry to ensure worker safety and prevent occupational diseases. This study examines the implementation of legal protection for OSH at PT Geo Dipa Energi (Persero) Unit Dieng, focusing on the company's Health, Safety, and Environment (HSE) policies, compliance with labor regulations, and workplace risk management. PT Geo Dipa Energi enforces various safety measures, including HSSE (Health, Safety, Security, and Environment) mandatory procedures, OSH training programs, and social security coverage through BPJS Employment and BPJS Health. The findings indicate that the company’s OSH management aligns with national regulations and international standards such as ISO 45001. However, several challenges persist, including a lack of discipline in using personal protective equipment (PPE), potential exposure to toxic gases such as hydrogen sulfide (H₂S), high noise levels from machinery, and inadequate ventilation. These factors pose significant risks to workers’ health and productivity. To address these challenges, PT Geo Dipa Energi has implemented the Hazard Observation (OrBa) program, which encourages employees to actively identify and report workplace hazards. This initiative aims to foster a stronger safety culture and enhance proactive risk management. By continuously improving its OSH strategies, PT Geo Dipa Energi is committed to ensuring a safer, healthier, and more compliant work environment, ultimately minimizing workplace hazards and improving operational sustainability.